EVALUASI PELAKSANAAN PENGAWASAN PENERIMAAN PAJAK PERTAMBAHAN NILAI (PPN) ATAS KEGIATAN MEMBANGUN SENDIRI (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Batu) - Karima, Ahlisia (Jurnal Mahasiswa Perpajakan, 2014)
The Potency of Value Added Tax (VAT) of Buliding by Self Effort in Batu is big enough seen from enhancement of Batu City investment on 2013so it is necessary to evaluate the Admission control to increase VAT acceptance on Building by Self Effort in Pratama Tax Office Batu. The purpose of this study is to find out the plot of admission control based on Building by Self Effort in Pratama Tax Office and to find out the evaluation of acceptance admission control based on Building by Self Effort in Pratama Tax Office. First to analyzing VAT admission control of VAT of Building bySelf Effort and Second to analyzing the acceptance based on Building by self effort. The design on this study is descriptive qualitative. The result of the study indicate that the VAT supervision on Building by Self Effort is approriate to minister of finance regualtion No. 163/PMK/03/2012. VAT admission on BuildingÂ  by Self Effort on 2011-2013 has small contribution which is under 10%. Therefore, Pratama Tax Office Batu should maximize the supervision to increase the acceptance. Keywords : Â Value Added Tax, Value Added Tax of Building By Self Effort, Admission Control, Acceptance on Building by Self Effort